IMPLEMENTASI PEMBELAJARAN DIFERENSIASI DALAM MENGAKOMODASI KERAGAMAN KEBUTUHAN BELAJAR SISWA MI: STUDI KUALITATIF DI MI MA’ARIF NU INSAN CENDEKIA - Nisaa Unzylayka (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
The diversity of students’ learning needs in Madrasah Ibtidaiyah represents a pedagogical reality that requires the implementation of adaptive, inclusive, and learner-centered instruction. Differences in academic abilities, learning styles, interests, and learning readiness are often not optimally accommodated through conventional, uniform instructional approaches. Therefore, differentiated instruction is a relevant strategy, as it allows teachers to adjust learning content, processes, and products according to students’ individual characteristics. This study aims to describe and analyze the implementation of differentiated instruction in accommodating the diversity of students’ learning needs at MI Maarif NU Insan Cendekia. The research employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with teachers and students, and analysis of instructional documents. Data validity was ensured through source and method triangulation. The findings indicate that differentiated instruction was implemented through the mapping of students’ learning needs, flexible instructional strategies, and variations in learning activities and assessments. This implementation had a positive impact on students’ engagement, self-confidence, and responsiveness, and it strengthens constructivist and humanistic perspectives in Madrasah Ibtidaiyah learning.